Thermal Regime and Variations in the Island Permafrost Near the Northern Permafrost Boundary in Xidatan, Qinghai–Tibet Plateau - Yin, Guoan; Luo, Jing; Niu, Fujun; Lin, Zhanju; Liu, Minghao (Frontiers in Earth Science, 2021)
Although the thermal regime and degradation of permafrost on the Qinghai-Tibet Plateau (QTP) have been widely documented, little information exists regarding the island permafrost in the area. Ground temperatures were therefore measured for eight years (2013–2020) at a permafrost island and at two contrasting sites in the Xidatan region to elucidate the permafrost in this area. Results indicate that the ground temperatures in the island permafrost were markedly higher than those at the same depth in the nearby marginal permafrost and the interior continuous permafrost. In addition, a distinct increasing trend was observed in the ground temperature of the island permafrost over the past eight years, and warming was signficanty faster in the deep soil than in the topsoil, indicating a bottom–up degradation pattern in the island permafrost. Moreover, due to the persistent increase in the thickness of the active-layer and the decrease in the depth of permafrost table, the permafrost island abruptly disappeared in 2018, which may be attributed to the anomalously high air temperatures that occurred in 2016 and 2017. The results of this study may provide references for understanding of the thermal regime and degradation process of island permafrost on the QTP